N-Fenilmaleimidas: atividade antibacteriana e moduladora da resistência a drogas em Staphylococcus aureus - Borges, Nathalie Helen Paes Barreto (2013)
Compounds derived from plants or animals have been instrumental in the discovery of anti-infective drugs, and now many synthetic antimicrobial drugs based on structural models of substances of natural origin. Several chemical compounds, natural and synthetic, have been reported as inhibitors of efflux pumps, acting as important additional tools in drug development co-formulated with appropriate antibiotics. In this study were evaluated seven N-Fenylmaleimides (NFM), gently assigned by Dr. Valdir Cechinel Filho (UNIVALI), obtained by organic synthesis. The values of the minimum inhibitory and bactericidal concentrations (MIC and MBC) of N-Fenylmaleimides (NFM), antibiotics and compounds NAB, by the broth microdilution method.Were determined the values of minimum inhibitory concentrations (MIC) of NFM, antibiotics and compounds NAB. In modulation of drug resistance, the MIC of the antibiotic compounds and NAB were determined in the presence and absence of subinibitory concentrations of NFM. Both studies were supplemented with analysis of in silico ADMET parameters. The derivatives 3,4-Cl-NFM, NFM-4-Cl and 4-CH3-NFM showed moderate antibacterial activity with MIC of up to 64 μg/mL in MSSA and MRSA strains. In the assay of modulation of drug resistance, 4-NO2-NFM reduced by up to four times the MIC of the antibiotic tetracycline and erythromycin. The 4-CH3 NFM showed the best results, with a reduction in MIC of the antibiotics tetracycline (up to 4-fold), erythromycin (16-fold), some representatives of fluoroquinolones (up to 4-fold) and compounds NAB (up to 4 times). By reducing the MIC of ethidium bromide, 4-CH3 NFM is considered in fact as a putative inhibitor of the efflux system in bacteria. In the analysis of molecular modeling, derivatives 3,4-Cl-NFM and 4-CH3-NFM, improved antibacterial and modulator compounds respectively, showed a profile with low toxic risk theoretical profile since they are promising to be used in drawing new derivatives more active and safer. The results presented here show that imidic derivatives may be used to potentiate the effect of antimicrobial agents to facilitate reintroduction of antibiotics currently ineffective for the clinical treatment of multiresistant infections.